2016
DOI: 10.18632/oncotarget.10150
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic vacuolization in cell death and survival

Abstract: Cytoplasmic vacuolization (also called cytoplasmic vacuolation) is a well-known morphological phenomenon observed in mammalian cells after exposure to bacterial or viral pathogens as well as to various natural and artificial low-molecular-weight compounds. Vacuolization often accompanies cell death; however, its role in cell death processes remains unclear. This can be attributed to studying vacuolization at the level of morphology for many years. At the same time, new data on the molecular mechanisms of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
247
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(262 citation statements)
references
References 303 publications
(353 reference statements)
8
247
3
4
Order By: Relevance
“…18,21,33 We observed that δ-TT induces morphological changes, with an intense cytoplasmic vacuolation in both CRPC cells. 18,21,33 We observed that δ-TT induces morphological changes, with an intense cytoplasmic vacuolation in both CRPC cells.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…18,21,33 We observed that δ-TT induces morphological changes, with an intense cytoplasmic vacuolation in both CRPC cells. 18,21,33 We observed that δ-TT induces morphological changes, with an intense cytoplasmic vacuolation in both CRPC cells.…”
Section: Discussionmentioning
confidence: 64%
“…52,53 TTs (specifically γ-and δ-TT) were shown to induce apoptosis by triggering the ER stress branches in cervical cancer, 30 breast cancer 54 and melanoma cells. 18,20,33 This makes these types of cell death a promising target for novel therapeutic strategies. 55,56 Here, we also observed that abrogation of apoptosis by the pancaspase inhibitor Z-VAD-FMK significantly, but not completely, reverted the cytotoxic effect of δ-TT on CRPC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3c). Vacuole formation in mammalian cells is a well-known morphological phenomenon when cells are exposed to kinds of pathogens and compounds, and always accompanies cell death [14]. …”
Section: Resultsmentioning
confidence: 99%
“…Cell death is classified into several types, such as apoptosis, necrosis (necroptosis), autophagy‐associated death, mitotic catastrophe, paraptosis and oncosis . Paraptosis has been characterized by cytoplasmic vacuolization that associates with extensive swelling of endoplasmic reticulum (ER), and mitochondria in some cases, in the absence of typical apoptotic features such as formation of apoptotic bodies and nuclear fragmentation . Several reports have shown that paraptosis or paraptosis‐like cell death (PLCD) is induced by overexpression of oncogenic genes, mutation or deletion of genes related to ER function, and exposure to natural or synthetic compounds .…”
mentioning
confidence: 99%